Synergistic Effect of NiLDH@YZ Hybrid and Mechanochemical Agitation on Glaser Homocoupling Reaction - Mokhtar, Mohamed; Alzhrani, Ghalia; Aazam, Elham S.; Saleh, Tamer S.; Al‐Faifi, Sulaiman; Panja, Subir; Maiti, Debabrata (Chemistry : a European journal, 2021)
Herein, we report the synthesis of nickel‐layered double hydroxide amalgamated Y‐zeolite (NiLDH@YZ) hybrids and the evaluation of the synergistic effect of various NiLDH@YZ catalysts and mechanochemical agitation on Glaser homocoupling reactions. Nitrogen adsorption‐desorption experiments were carried out to estimate the surface area and porosity of NiLDH@YZ hybrids. The basicity and acidity of these hybrids were determined by CO2‐TPD and NH3‐TPD experiments respectively and this portrayed good acid‐base bifunctional feature of the catalysts. The NiLDH@YZ‐catalyzed mechanochemical Glaser coupling reaction achieved best yield of 83 % for the 0.5NiLDH@0.5YZ hybrid after 60 min of agitation, which revealed the highest acid‐base bifunctional feature compared to all the investigated catalysts. The developed catalyst has proven itself as a robust and effective candidate that can successfully be employed up to four catalytic cycles without significant loss in catalytic activity, under optimized reaction conditions. This work demonstrated a new strategy for C−C bond formation enabled by the synergy between mechanochemistry and heterogeneous catalysis. In the present study, NiLDH, YZ and amalgamated NiLDH@YZ catalysts were tested for the Glaser homocoupling reaction. The catalyst 0.5NiLDH@0.5YZ showed superior catalytic efficiency under mechanochemical agitation. This robust catalyst used for four times provides a new strategy in C−C coupling reactions by using mechanochemistry.